Monitoring seasonal and long-term changes in test performance in elite swimmers - Anderson, M. E.; Hopkins, W. G.; Roberts, A. D.; Pyne, D. B. (European Journal of Sport Science, 2006)
The purpose of this study was to characterize changes and variability in test performance of swimmers within and between seasons over their elite competitive career. Forty elite swimmers (24 male, 16 female) performed a 7×200-m incremental swimming step test several times each 6-month season (10±5 tests, spanning 0.5-6.0 y). Mixed linear modeling provided estimates of percent change in the mean and individual responses (within-athlete variation as a coefficient of variation) for measures based on submaximal performance (fixed 4-mM lactate), maximal performance (the seventh step) and lean mass (from skinfolds and body mass). Submaximal and maximal swim speed increased within each season from pre to taper phase by 2.2% for females and 1.5% for males (95% confidence limits ±1.0%), with variable contributions from stroke rate and stroke length. Most of the gains in speed were lost in the off-season, leaving a net average annual improvement of 1.0% for females and 0.6% for males (±1.0%). For submaximal and maximal speed, individual variation between phases was ±2.2% and the typical measurement error was ±0.80%. Step test and anthropometric measures can be used to confidently monitor progressions in swimmers in an elite training program within and between seasons.